Th1 ‐ CD11c+ B Cell Axis Associated with Response to Plasmapheresis in Multiple Sclerosis. Issue 4 (27th September 2021) - Kimura, Kimitoshi; Lin, Youwei; Yamaguchi, Hiromi; Sato, Wakiro; Takewaki, Daiki; Minote, Misako; Doi, Yoshimitsu; Okamoto, Tomoko; Takahashi, Ryosuke; Kondo, Takayuki; Yamamura, Takashi
Abstract : Objective: Although plasmapheresis is a treatment option for patients with autoimmune neurological diseases, treatment response varies greatly among patients. The main objective of this study was to find out if biological/immune traits correlate with a beneficial response. Methods: We thoroughly analyzed immune phenotypes in paired blood samples from a cohort of 31 patients with multiple sclerosis before and after plasmapheresis, in parallel with clinical evaluation of treatment response. Results: The frequency of IFN‐γ + Th1 cells was persistently higher in those who obtained benefit from plasmapheresis (responders) than nonresponders. The Th1 cell frequency before plasmapheresis provided a high predictive value for beneficial response, achieving area under the curve (AUC) of 0.902. Plasmapheresis treatment decreased inflammation‐related gene expressions in Th1 cells. Meanwhile, IFNG expression in Th1 cells positively correlated with the frequency of CD11c + B cells, of which a pathogenic role has been suggested in several autoimmune diseases. In line with this, in vitro experiments showed that CD11c + B cells would increase in response to exogenous IFN‐γ compared to IL‐4, and secrete high amounts of IgG. B cell receptor analysis indicated that clonal expansion of CD11c + B cells takes place in patients with multiple sclerosis. Interestingly, CD11c + B cells, which showed unique gene expression profile, decreased after plasmapheresis treatment along with all the immunoglobulin subsets in the circulation. Interpretation: Taken together, we postulate that Th1 cell ‐ CD11c + B cell axis is involved in treatment response to plasmapheresis, giving us clues to better understanding of complicated pathogenesis of autoimmune diseases, and getting closer to a personalized therapy. ANN NEUROL 2021;90:595–611